Changes in menstrual cycles among Iranian women during the COVID-19 pandemic: A cross-sectional study - Fahimeh Ranjbar; Shima Haghani; Motahareh Aghashahi; Maryam Gharacheh (Shahid Sadoughi University of Medical Sciences, 2024)
Abstract Background: Some women experienced alterations in their menstrual cycles during the Coronavirus disease 2019 (COVID-19) pandemic. Objective: This study aimed to evaluate the changes in menstrual cycles among Iranian women during the COVID-19 pandemic. Materials and Methods: This cross-sectional study included 1500 women of childbearing age referred to healthcare centers in Tehran, Iran from April-November 2022. Participants were selected using the stratified sampling method. Data were collected via a questionnaire covering information on menstrual cycle, COVID-19 infection, and COVID-19 vaccination status. The study's outcomes focused on menstrual changes by evaluating cycle regularity, duration, and symptoms based on participant-reported observations. Results: The findings revealed that the pattern of menstrual change during the pandemic occurred in the form of a shorter interval in 8.6%, and longer interval in 8.9%, shorter duration in 10.4%, longer duration in 9.4%, heavier bleeding in 12.3%, lighter bleeding in 14.7%. The chance of menstrual changes in women who were infected with COVID-19 was 54% higher than that of women who were not infected, and the chance of menstrual changes in women who received 3 doses of COVID-19 vaccine was 1.5 times higher than women who had not been vaccinated. Conclusion: Our research revealed a high incidence of menstrual changes among Iranian women of childbearing age during the COVID-19 pandemic. Healthcare providers should be knowledgeable about the menstrual changes associated with COVID-19 infection and vaccination to provide information and support to affected women.